Adenosine-A2A Receptor Pathway in Cancer Immunotherapy - Sun, Changfa; Wang, Bochu; Hao, Shilei (Frontiers in Immunology, 2022)
A2A receptors (A2AR), a typical GPCR with a high affinity for adenosine, was expressed in many immune cells, such as regulatory T cells, cytotoxic T cells, macrophages, etc. Adenosine binding to the A2AR receptor activates the typical G protein and triggers the cAMP/PKA/CREB pathway. The adenosine-A2AR pathway plays an important role in protecting normal organs and tissues from the autoimmune response of immune cells. However, many solid tumors hijack the adenosine-A2AR pathway by promoting adenosine accumulation. The activation of the A2AR pathway inhibited the immune response of immune cells and then promotes the immune escape of tumor cells in the tumor microenvironment. Recently, both animal experiments and clinical trials indicated that blocking the adenosine pathway can inhibit the progression of a variety of solid tumors. In addition, it is encouraging that A2AR blockade combined with CAR T cells therapy showed better anti-tumor efficacy. Therefore, this review will discuss the role of the adenosine-A2AR pathway in the tumor microenvironment and summarize recent advances of A2AR-cancer related studies.